Differential effects of SARM1 inhibition in traumatic glaucoma and EAE optic neuropathies - Pingting Liu; Wei Chen; Haowen Jiang; Haoliang Huang; Liping Liu; Fang Fang; Liang Li; Xue Feng; Dong Liu; Roopa Dalal; Yang Sun; Paymaan Jafar-Nejad; et al. (Elsevier, 2023)
Optic neuropathy is a group of optic nerve (ON) diseases with progressive degeneration of ON and retinal ganglion cells (RGCs). The lack of neuroprotective treatments is a central challenge for this leading cause of irreversible blindness. SARM1 (sterile α and TIR motif-containing protein 1) has intrinsic nicotinamide adenine dinucleotide (NAD+) hydrolase activity that causes axon degeneration by degrading axonal NAD+ significantly after activation by axon injury. SARM1 deletion is neuroprotective in many, but not all, neurodegenerative disease models. Here, we compare two therapy strategies for SARM1 inhibition, antisense oligonucleotide (ASO) and CRISPR, with germline SARM1 deletion in the neuroprotection of three optic neuropathy mouse models. This study reveals that, similar to germline SARM1 knockout in every cell, local retinal SARM1 ASO delivery and adeno-associated virus (AAV)-mediated RGC-specific CRISPR knockdown of SARM1 provide comparable neuroprotection to both RGC somata and axons in the silicone oil-induced ocular hypertension (SOHU) glaucoma model but only protect RGC axons, not somata, after traumatic ON injury. Surprisingly, neither of these two therapy strategies of SARM1 inhibition nor SARM1 germline knockout (KO) benefits RGC or ON survival in the experimental autoimmune encephalomyelitis (EAE)/optic neuritis model. Our studies therefore suggest that SARM1 inhibition by local ASO delivery or AAV-mediated CRISPR is a promising neuroprotective gene therapy strategy for traumatic and glaucomatous optic neuropathies but not for demyelinating optic neuritis.